PEARLS Randomized Lifestyle Trial in Pregnant Hispanic Women with Overweight/Obesity: Gestational Weight Gain and Offspring Birthweight [Corrigendum] - Trak-Fellermeier MA (Dove Medical Press, 2020)
Trak-Fellermeier MA, Campos M, Meléndez M, et al. Diabetes Metab Syndr Obes. 2019;12:225–238. On page 225, Abstract, Results subheading, “Although not statistically significant, women in the intervention group (6/15) were 1.7 times more likely to achieve appropriate weekly GWG until delivery when compared with controls (4/16 women) (adjusted incidence rate ratio = 1.67; 95% CI: 0.40, 6.94).” should read “Although not statistically significant, women in theintervention group (6/15) were 1.7 times more likely to achieve appropriate total GWG until delivery when compared with controls (4/16 women) (adjusted incidence rate ratio = 1.67; 95% CI: 0.40, 6.94).” Appropriate GWG (baseline to delivery) section, 2nd to 4th line on page 230, “Forty percent (6/15) of women in the interventionachieved appropriate GWG/week compared with 25%(4/16) in the control group.” should read “Forty percent (6/15) ofwomen in the intervention achieved appropriate total GWG compared with 25% (4/16) in the control group.” The authors apologize for not noticing the inconsistencies between the text and Table 3 earlier.   Read the original article